OER for Inclusive and Equitable Quality Education: from Commitment to Action - Asia e University, AeU (AeU, 2016)
The consultations are being held in partnership with UNESCO, Slovenian National Commission for UNESCO and UNESCO Chair on Open Technologies for OER and Open Learning (Jožef Stefan Institute, Slovenia), and with the generous support of The William and Flora Hewlett Foundation.The Asia Consultation, held in Kuala Lumpur is the first of six Regional Consultations that will be conducted around the world by COL in the lead up to the 2nd World Open Educational Resources (OER) Congress, scheduled to be held in Ljubljana, Slovenia, from 18th to 20th September 2017. The other Regional Consultations are:- 1. Middle East and North Africa, Qatar Foundation, 26-27th February 2017; 2. Americas, UNICAMP, 3rd-4th April 2017; 3. Europe, Malta Ministry for Education and Employment, 23rd – 24th February 2017; 4. Africa, Ministry of Education, 2nd-3rd March 2017; 5. Pacific, Open Polytechnic of New Zealand, 29th-30th May 2017